Optimizing The Role of Religious Jurisdiction in Preventing Child Marriage in Gorontalo Province - Aliyas Aliyas; Suardi Rais; A. ST. Kumala Ilyas; Jupri Jupri; Yoslan K Koni (Jurnal Hukum Volkgeist, 2022)
The prevalence of child marriage under 18 years released by the Central Bureau of Statistics in 2020 places Gorontalo Province in the 6th highest place in Indonesia with a rate of 23.16%. The data is corroborated by the records of the Supreme Court who receive cases of requests for dispensation from marriage which each year has increased. the religious court's allusion to child marriage through a marriage dispensation mechanism. A quo mechanism is regulated in Supreme Court Regulation (PERMA) Number 5 of 2019 concerning Guidelines for Trialing Applications for Dispensation of Marriage. Various factors behind the request for underage marriage include: because they really want to get married, because they are pregnant out of wedlock and there are applications for girls whose age has not been justified by law. On the basis of these problems, this study aims to provide space for the religious court as the final determinant through legal considerations and its sociological aspects, prioritizing prevention efforts by narrowing the space for applications, examining cases more carefully, and the commitment of the parties to respond to the negative consequences of child marriage. The research method used is the legal behavior approach that occurs in society (socio legal research).